Analisis Kelayakan Finansial Usaha Tani Lada Masyarakat Perkebunan di Kabupaten Kolaka - Supriono; Rayuddin Rayuddin; Muhammad Nur (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
Abstract. Pepper farming has an important and strategic role in increasing the income of the pepper plantation community in East Kolaka Regency, however, smallholder pepper plantations are still characterized by various weaknesses such as relatively narrow farming land, conventionally cultivated with low productivity and quality, and a weak position in product marketing. This study aims to examine the financial feasibility and sensitivity of pepper farming in East Kolaka District, Southeast Sulawesi Province. The designated research location is Tirawuta District as a pepper production center in the pepper plantation community in East Kolaka Regency. Sampling was carried out purposively based on the age of the plants, ie 1 to 17 years old. The data were analyzed using a quantitative descriptive analysis method using a feasibility analysis through the Benefit-Cost approach in PAM and sensitivity analysis. The results showed that financially, the pepper farming of plantation communities in East Kolaka Regency was feasible and profitable as evidenced by a B/C value of 1.10 and an NPV value of IDR 48,429,250.00.-. The results of the sensitivity analysis with the scenario if inorganic fertilizers are not subsidized by the government show a decrease in farmers' profits by 17,4 %, but smallholder pepper farming is still feasible to cultivate